(untitled) (Research, Society and Development, 2024)
Acne is a chronic and multifactorial disease involving inflammation of the pilosebaceous units. For moderate to severe forms of acne that do not respond to conventional therapy, oral isotretinoin is the most indicated therapy by dermatologists. A retinoid compound derived from vitamin A, highly effective in acne treatment, acts on the main causes implicated in its pathogenesis. However, some laboratory alterations may be observed with its use. This study aimed to identify laboratory alterations that may occur in the lipid profile (TG and TC) and liver function (ALT and AST) in acne patients undergoing isotretinoin treatment. It is an integrative literature review based on scientific articles indexed in the MEDLINE/PubMed, SciELO, and LILACS databases over the last five years, using the keywords "acne" and "isotretinoin". The prevalence of laboratory abnormalities related to isotretinoin use revealed variations among studies, however, predominantly, there was an increase in levels of the analytes TG, TC, ALT, and AST. Additionally, a discrepancy was observed in the recommendation of monitoring frequency among the evaluated authors. Most studies indicated that the alterations in the analytes in question were mild, transient, and reversible in nature, often normalizing after treatment completion. Overall, the studies suggest that frequent monitoring may be more relevant for overweight patients or those with specific risk factors, while reduced frequency may be appropriate for most patients, given the low occurrence of clinically significant alterations.